Comparison of capabilities to implement REST services in Java language using the popular web application frameworks. - Kwiatkowski, Rafał; Kopniak, Piotr (Journal of Computer Sciences Institute, 2018)
This article presents the results of a comparison of capabilities and efficiency of REST in Java using frameworks such as Jersey, Apache CXF and Spring MVC. Comparative analysis was conducted on the basis of application implemented by each of the above frameworks. Application have been implemented using technologies such as Spring Boot, Hibernate, Maven, and MySQL.